Bastroviruses (Astroviridae): genetic diversity and potential impact on human and animal health - German V. Roev; Nadezhda I. Borisova; Nadezhda V. Chistyakova; Anastasia V. Vyhodtseva; Vasiliy G. Akimkin; Kamil F. Khafizov (Вопросы вирусологии, 2023)
Introduction. Bastroviruses were discovered in the Netherlands in 2016 in human stool samples and show partial genetic similarities to astroviruses and hepatitis E viruses. Their association with disease onset has not yet been established.